miR-351 promotes atherosclerosis in diabetes by inhibiting the ITGB3/PIK3R1/Akt pathway and induces endothelial cell injury and lipid accumulation - Hong Li; Dan Song; Qihui Liu; Linlin Li; Xiaoshi Sun; Jiamei Guo; Dianlian Li; Ping Li (Molecular Medicine, 2022)
Abstract Background The miR-351 gene is significantly upregulated in diabetic mice with atherosclerosis. However, the mechanism by which its presence is important for the overall disease has not been elucidated. Therefore, this study will investigate the mechanism of miR-351 in the process of diabetes mellitus with atherosclerosis through miR-351 gene knockout mice. Methods In this study, miR-351−/− C57BL/6 mice were first induced to form a type 2 diabetes mellitus model with atherosclerosis by STZ injection and a high-fat diet. Pathological tests (oil red O, HE, and Masson staining) combined with biochemical indices (TC, TG, LDL-C, HDL-C, TNF-α, hs-CRP, NO, SOD, MDA, CAT, and GSH-Px) were performed to evaluate the pathological degree of atherosclerosis in each group. Mouse aortic endothelial cells were treated with oxidized low-density lipoprotein (ox-LDL) and 30 mM glucose to establish a diabetic atherosclerosis cell model. Combined with cell oil red O staining and flow cytometry, the effects of silencing miR-351 on lipid accumulation and cell apoptosis in the diabetic atherosclerosis cell model were determined. Fluorescence in situ hybridization was used to detect the localization and transcription levels of miR-351 in cells. The target genes of miR-351 were predicted by bioinformatics and verified by dual-luciferase activity reporting. Western blotting was used to detect the expression levels of phosphorylated inosine 3-kinase regulatory subunit 1 (PIK3R1)/serine/threonine kinase 1 (Akt) and apoptosis-related proteins after transfection with integrin subunit β3 (ITGB3) small interfering ribonucleic acid (siRNA). Results The expression of the miR-351 gene was significantly increased in the high-fat wild-type (HWT) group, and its expression was significantly decreased in the knockout mice. Silencing miR-351 effectively alleviated atherosclerosis in mice. The levels of miR-351 expression, apoptosis, lipid accumulation, and oxidative stress in ox-LDL + high glucose-induced endothelial cells were significantly increased. These phenomena were effectively inhibited in lentivirus-infected miR-351-silenced cell lines. Bioinformatics predicted that miR-351-5p could directly target the ITGB3 gene. Transfection of ITGB3 siRNA reversed the downregulation of apoptosis, decreased oil accumulation, and decreased oxidative stress levels induced by miR-351 silencing. In addition, it inhibited the activation of the PIK3R1/Akt pathway. Conclusion Silencing miR-351 upregulates ITGB3 and activates the PIK3R1/Akt pathway, thereby exerting anti-apoptosis and protective effects on endothelial cells.